Ovarian cyst mimicking acute appendicitis in children: a case report - Noor, Hafni Zuchra; Wahyuni, Alfaina; Retnowati, Sulistiari (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2024)
Pediatric acute appendicitis is common; however, it is different from torsion ovarian cysts. The estimated incidence of ovarian torsion in children is 5 per 100,000 girls. Herein, we report two cases of ovarian torsion mimicking pediatric acute appendicitis mimicking ovarian cyst. In the first case, a girl who was being assessed for acute appendicitis was identified to have torsion of the ovarian cyst during the surgery. In the second case, a girl experienced a ruptured ovarian cyst but then got severe appendicitis following the surgical procedure. The simultaneous occurrence of appendicitis and ovarian cysts is rare. These two patients' acute gastrointestinal complaints and symptoms exhibit similarities and may coincide. Both patients underwent salpingo-oopherectomy and appendectomy. Both patients were healthy on hospital discharge in a healthy condition. Female patients with severe abdominal pain and amenorrhea should be evaluated for ovarian torsion. Diagnosing the condition may be challenging due to non-specific clinical signs.